The Role of Tiktok Social Media in Increasing Students Interest Entrepreneurship - Melia Br Ginting; Muhammad Irwan Padli Nasution; Nurbaiti Nurbaiti (Universitas Bina Sarana Informatika, 2024)
The aim of this research is to determine the role of TikTok social media in increasing students' interest in entrepreneurship. The problem is that many students are not very good at entrepreneurship, judging from their many needs; therefore, students who want to start a business should be able to do so by taking advantage of existing online innovation and entertainment, because now everyone can definitely access and even have a virtual entertainment account that can be used to share data in the form of photos and recordings. TikTok is an online entertainment service that is generally popular among millennials for doing business. This research method used a quantitative approach. The population in this study was students at UIN North Sumatra, with a total of 100 respondents using a purposive test. Information collection methods use questionnaires, and data analysis techniques use e-views and multiple linear regressions. The test results show that the dependent variable TikTok web-based entertainment (X), more or less and at the same time has a significant effect on the independent factor Business Interest (Y), this tends to be reasonable that the TikTok virtual entertainment variable influences interest in business ventures. The collateral coefficient (R Square), and it means that every 1% increase in TikTok web-based entertainment increases business interest by 41.3%. Meanwhile, the impact of recognizing traditional assumptions shows that the model conditions do not suffer from the adverse effects of multicollinearity problems, do not contain heteroscedasticity, and show normal conditions.